The strawberry thief - Harris, Joanne, 1964- (Harris, Joanne, 1964- Chocolat, 2019)
The compelling new novel from the author of the bestselling Chocolat. Vianne Rocher has settled down. Lansquenet-sous-Tannes, the place that once rejected her, has finally become her home. With Rosette, her 'special' child, she runs her chocolate shop in the square, talks to her friends on the river, is part of the community. Even Reynaud, the priest, has become a friend. But when old Narcisse, the florist, dies, leaving a parcel of land to Rosette and a written confession to Reynaud, the life of the sleepy village is once more thrown into disarray. The arrival of Narcisse's relatives, the departure of an old friend and the opening of a mysterious new shop in the place of the florist's across the square - one that mirrors the chocolaterie, and has a strange appeal of its own - all seem to herald some kind of change: a confrontation, a turbulence - even, perhaps, a murder...